Meningkatkan Kesadaran Hukum Masyarakat Melalui Sosialisasi Lembaga Bantuan Hukum Samudra Muara Sabak - Dedi Mizwar; Erwina Kartika Devi; Al-Munip; Kurniawan; Siti Marfu'ah (CV. Akira Java Bulu, 2025)
Legal awareness within society is a fundamental factor in establishing an orderly, just, and civilized social life. However, in the Muara Sabak area, many community members still lack an understanding of their legal rights and obligations and remain unaware of the mechanisms to obtain free legal aid. In response to this condition, a community service program was carried out by the Lembaga Bantuan Hukum (Legal Aid Institute) Samudra Muara Sabak, aiming to enhance public understanding and legal awareness through the socialization of the institution’s roles and services. The methods employed included lectures, interactive discussions, and simple case simulations designed in a participatory and communicative manner. The results demonstrated a significant increase across all aspects measured through pre- and post-activity evaluations, particularly in understanding the right to legal aid, knowledge of legal aid institutions, and awareness of resolving issues through lawful means. The average improvement of 40–45% indicates the effectiveness of the socialization method in bridging the information gap between the community and formal legal institutions. Beyond improving knowledge, the program also encouraged behavioral changes, as participants became more inclined to pursue legal channels for conflict resolution and actively disseminate legal information within their communities. Thus, this activity not only strengthened the role of LBH Samudra Muara Sabak as a strategic partner in legal empowerment but also made a tangible contribution to fostering a fair, rational, and civilized legal culture as the foundation for developing a legally conscious society within a democratic state framework.